TOURISM DEVELOPMENT DISTORTS THE BALINESE CULTURE? (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2004)
Attitudes toward tourism development vary greatly among different approaches. To cautionary approach, this inter-nation phenomenon is seen as fruiting a hulk of various physical and social excess. To others, adaptation and scientific approaches, when well planned, organized, implemented, and controlled. tourism development can bear lots of advantages both to the tourists and host countries. In Bali, many researchers from different scientific backgrounds found enough empirical evidence that tourism development generates numbers of beneficial influence for the development of the Balinese culture.